Workers’ lead exposure in informal batteries factories - V Ramírez, Augusto (2008)
Introduction: Work with lead is a universal industrial problem, especially when done without labor hygiene approach. Lead Peruvian’s mining and metallurgy maintains good quality programs for management of occupational health, but informal Peruvian industry does not. Objectives: To determine the actual heath status of handicraft and informal batteries factories workers using blood lead levels as exposition indicators. Design: Observational and transversal study. Setting: Ilo, Peru’s Occupational Health Service Hospital. Participants: Workers at four handicraft informal batteries factories. Interventions: Information was obtained from 41 workers by direct interview, from August 1999 through January 2000. For blood lead levels determination we used atomic absorption spectrophotometry with graphite oven, and for hemoglobin, microhematocrit. We obtained percentages, averages, ranges, and standard deviations. We compared blood lead levels with health and occupational hygiene variables. Main outcome measures: Blood lead and saturnism symptoms association. Results: Group average age was 35 years (range. 16 to 52), work time average, 6,5 years. Blood lead level: 37,7 [± 17,7] ug/dL (range: 13.5 to 72,3). Mean hemoglobin: 11,2 [± 1,1] g/dL (range: 8,9 to 13,2). We found significant statistical association between blood lead level >30 ug/dL and occupational lead poisoning, work as welder-caster and worse habits of occupational hygiene. Conclusions: Worker’s health is affected in this occupational group. Blood lead levels exceeded permissible levels for exposed workers and they showed anemia.